A long-term view of knowledge agents as key enablers of environmental knowledge - Martínez Martínez, Aurora; Cegarra-Navarro, Juan Gabriel; Wensley, Anthony (Proceedings of the European Conference on Knowledge Management, ECKM, 2020)
Knowledge agents are individuals who contribute to the transformation and exchange of knowledge and who make active use of the knowledge derived from relevant information. From a hotel perspective, knowledge agents are individuals who can provide external and internal information to deal with environmental issues. In this paper, customers, managers, employees and tour operators/travel agents who are responsible for hotel operations are referred as 'knowledge agents'. These agents develop and enhance their own knowledge and that of the organization in order to ensure that appropriate actions are taken to deal with environmental issues and potentially enhance the environmental knowledge of the firm. This study examines the role played by knowledge agents as key enablers of the processes of creating and updating the environmental knowledge of an organisation. The paper also examines the relationship between environmental knowledge and business performance. These relationships are examined through an empirical study of 87 companies in the Spanish hospitality sector. The results of the study indicate that the role played by knowledge agents at any given time (T) not only is significant in predicting environmental knowledge at that time but they also play a significant role in updating environmental knowledge at a later point in time (in this study T+6 years).
Conferencia de "18th European Conference on Knowledge Management, ECKM 2017; International University of CataloniaBarcelona; Spain; 7 September 2017 through 8 September 2017"
Keywords: knowledge agents; environmental knowledge; hospitality industry; performances and time; Scopus(2); WOS(2)